2009
DOI: 10.1007/s12525-009-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organizational culture on the use of ICT for knowledge management

Abstract: The paper aims at analyzing the influence of diverse organizational cultures on the use of ICT for strategic KM. By combining literature from different areas, namely strategic KM, ICT for KM, organizational culture and effectiveness, a theoretical model is proposed and tested in a sample of more than 300 firms in Spain. Results show that diverse organizational cultures (hierarchy, clan, adhocracy and market) are found to impact on the use of ICT for strategic KM (personalization and codification) differently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
4
18
0
1
Order By: Relevance
“…Specifically, both teams frequently used teleconferencing to enable distributed knowledge sharing sessions suggesting the importance of teleconferencing tools for GDSDT to share knowledge during the requirements analysis phase as well as the software development/ maintenance phase. This concurs with the findings from past research which has acknowledged the important role facilitated by ICT in supporting knowledge management initiatives [22]. Further, it was reported that knowledge sharing sessions will be most effective in distributed teams when members have accurate knowledge of ''who knows what'' in the group and when members share their unique knowledge resources freely with other members [2].…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, both teams frequently used teleconferencing to enable distributed knowledge sharing sessions suggesting the importance of teleconferencing tools for GDSDT to share knowledge during the requirements analysis phase as well as the software development/ maintenance phase. This concurs with the findings from past research which has acknowledged the important role facilitated by ICT in supporting knowledge management initiatives [22]. Further, it was reported that knowledge sharing sessions will be most effective in distributed teams when members have accurate knowledge of ''who knows what'' in the group and when members share their unique knowledge resources freely with other members [2].…”
Section: Discussionsupporting
confidence: 89%
“…Jasimuddin and Hasan (2015) suggest that identifying a specific type of organizational culture that supports knowledge sharing is much important as the actual practice of knowledge transfer (Durmusoglu et al, 2014;Lopez-Nicolas & Meroño-Cerdán, 2009). Thus, if one wants to predict the kind of behavior that would be followed by organizational members when it comes to transfer of knowledge, the type of organizational culture adopted by an organization would determine it.…”
Section: Organizational Culture and Knowledge Sharingmentioning
confidence: 99%
“…Hierarchy culture supports the mechanistic governance approach through formal rules, norms, policies and procedures (Lopez-Nicolas & Meroño-Cerdán, 2009). Paro and Gerolamo (2017) found that hierarchy culture characterized as formal and structured governs the behavior of people through rules and procedures.…”
Section: Organizational Culture and Knowledge Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a positive association between hierarchical cultures and successful deployment of SDMs and a negative associative between rational (market) cultures and successful deployment. Lopez-Nicolas and Merono-Cerdan [22] looked at the impact of organizational culture on the use of ICT for knowledge management (e.g. computer supported cooperative work).…”
Section: B It Culturementioning
confidence: 99%